Onion Varieties (Allium Ascalonicum L.) Test With Application Of Several Kinds Microbia Consortium Its Influence On Growth and Yield - Dewi, Tyas Soemarah Koernia; Budiyono, Agus; Supriyadi, Teguh; Suprapti, Endang; Putro, Herdyanto; siti mardhika sari (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2024)
Shallots are one of the horticultural commodities that Indonesian people need. The use of bacterial consortia in shallot cultivation is expected to be useful for increasing soil fertility due to soil biochemical processes. This research aims to determine the effect of applying a microbial consortium from several products to the growth and yield of several shallot varieties. This research was carried out using a Split Plot Design with a split plot method which consists of two factors, namely: 1. Red onion variety, (V1: local rubber variety; V2: white local variety; V3: local Javanese varieties), 2. Types of decomposing plants (microbial consortium), : (P0: Control; P1: M21; P2: EM4; P3: Beka Decomposer). The research results showed: (1) The variety test showed very significant plant height, number of leaves, fresh stover weight, dry stover weight, tuber diameter, fresh tuber weight per bunch, tuber dry weight per bunch, and tuber dry weight per plot. However, there was no real difference between the number of bulbs per plant and the number of bulbs per plot. (2) The combination of microbial consortia with shallot varieties showed significantly different results regarding the number of leaves and bulb diameter. However, there were no real differences in plant height, fresh stover weight, dry stover weight, number of tubers per plant, number of tubers per plot, fresh weight of tubers per bunch, dry weight of tubers per bunch and dry weight of tubers per bunch. (3) The research results showed that the highest yield was obtained from the combination of V2P1 with the treatment of local white varieties of shallots and the application of the M21 microbial consortium with an average value of 150.27 g/plot (16,905 kg/ha or 16.9 tons/ha).